Characterization of miR-3099-mediated posttranscriptional of target genes regulation during neurogenesis in mice - Zainal Abidin, Shahidee (2019)
MicroRNAs (miRNAs) are a family of small non-coding RNAs with potent regulatory roles in metabolism, neurodevelopment, neuroplasticity, apoptosis, and other neurobiological processes. MiRNAs function through partial complementary base-pairing with specific target mRNAs, resulting in the repression of translational processes or the promotion of mRNA deadenylation leading to degradation. In 2011, miR-3099 was found to be expressed as early as in the blastocyst stage, in which the expression was maintained until the developing E11.5 mouse brain. The expression of miR-3099 was further restricted to the cortical plate of the developing mouse brain between E13.5 and E17.5, coinciding with the time that the majority of the cells are committed to neuronal cell lineage. Moreover, the miR-3099 was also found to be highly expressed in differentiating P19 cell (2-fold upregulation) when comparing to the proliferating P19 cell. Therefore, this study aims to understand the role of miR-3099 during neuro-differentiation and corticogenesis in the mouse model. The expression of miR-3099 was found elevated by 2-3 folds in 46C mouse embryonic stem (mES) cell upon neural induction. Then, predicted target gene of miR-3099 was further analysed by using four different prediction algorithms (miRDB, miRanda, TargetScan and DIANA-micro-T-CDS) and DAVID bioinformatics analysis with emphasis on target genes related to brain development and function. Based on the prediction, nearly 70% of the predicted target genes were expressed in the nervous system. Of these predicted target genes, Gfap was chosen as a candidate for downstream validation because it had been implicated in an important pathway in the brain known as the JAK-STAT signalling pathway, which controls the onset of astrocyte formation. By using the luciferase reporter gene system, Gfap was negatively inhibited by miR-3099. Furthermore, overexpression of miR-3099 was performed in vitro and in vivo for better understanding of the role of miR3099 during neuro-differentiation and brain development. In vitro, a transgenic mES cell that carried miR-3099 was overexpressed and differentiated for 17 days. The gene expression profile was carried out by using stem-loop RT-qPCR for different marker analysis such as proliferative, neural progenitor, neuron, astrocyte and oligodendrocyte markers. The analysis revealed that the overexpression of miR-3099 promoted neuronal differentiation and suppressed the astrogliogenesis in the in vitro system. In the in vivo system, the overexpression of miR-3099 caused disorganised neuronal migration potentially due to downregulation of Gfap. Heretofore, the human homologue of miR-3099 has not been found or reported. In silico analysis via seed sequence similarity search in GEO database found that mds21 to be novel miRNA that has 100% identical at seed region and 64% closed to miR-3099 mature sequence. Interestingly, the expression of mds21 was found to be expressed in various human cell line and tissue, including the brain suggesting that mds21 might be a potential miR-3099 homologue in the human genome. Collectively, this study has shown that miR-3099 plays an essential role in modulating and regulating key markers involved in neuronal differentiation and neural cell function. The degree of functional conservation between miR-3099 and mds21 is not clear, and further validations are needed to characterise them further.